Feu!: abécédaire des féminismes présents - Dorlin, Elsa (Libertalia, 2021)
Plutôt que de réduire le féminisme à des revendications faites à l’État, au patron, au chef ou à papa, pour plus de lois, plus de “sécurité”, à n’être que le porte-drapeau ou le cache-misère du capitalisme, de tel ou tel gouvernement nationaliste, ces histoires des féminismes présents rappellent et font résonner ensemble nos vies féministes. Ce livre fonctionne comme un abécédaire, un manuel, une boîte à outils, un dictionnaire amoureux, dans lequel échanger des idées, affûter des armes, écouter des voix, partager des expériences et des pratiques, vibrer pour des luttes présentes. Il s’adresse à tous·tes : il contient à la fois des ressources et foisonne de références utiles, de notions, mais il est fabriqué par des plumes et des voix, des points de vue situés sur des retours d’expériences collectives, des itinéraires politiques et intimes, des réflexions et des rétrospections sur des parcours, des engagements, des révoltes et des espoirs. En pluralisant les styles, en se situant à la fois du côté de la théorie et de la pratique, de la création, des écritures au “nous” et au “je”, il témoigne de la force d’une approche féministe de l’histoire intellectuelle et politique. Il est dédié à toutes les résistantes anonymes au quotidien des violences les plus crasses, à celles qui embrasent les tribunaux, cassent des genoux et brisent les vitrines, à celles qui inventent mille tactiques imperceptibles pour survivre et se mettre à l’abri, à la mémoire de celles dont les noms recouvrent les murs de nos villes la nuit, à la puissance des collectifs qui se font, à ceux qui se sont défaits, qui se sont (re)constitués ailleurs ou autrement, à ce qui nous lie.
L'article "Justice reproductive" de Bessaïh, Nesrine, 2021 a été donné en lecture au cours SEX2283. L'entrée "Cisgenre" d'Alexandre Baril a été donné en lcture au cours SOC2014.
Keywords: afro-féminisme; approches et analyses; corps; cours; droits des femmes*; fem3100; féminisme décolonial; féminismes noirs; genre; identités LGBTQIA2+; intersectionnalité; inégalités; outils; ouvrages de références; premier cycle; queer; racisme; sex2283; sexisme; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; écoféminisme

Futurs & Projections (FéminÉtudes, 2021)
FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; corps; féminétudes; genre; identités LGBTQIA2+; intersectionnalité; militance; personnes trans*; périodes historiques; queer; québec; régions géographiques; sexualité; thématiques; violences; écriture des femmes*

Associations between perceived discrimination and contraceptive method use: why we need better measures of discrimination in reproductive healthcare - Loder, Charisse; Hall, K.; Kusunoki, Yasamin; Harris, Lisa Hope; Dalton, Vanessa (Women & Health, 2021)
Discrimination has historically contributed to coercive contraceptive in the United States. We investigated associations between perceived discrimination, or the perception of unequal treatment in everyday life, and contraceptive method use among U.S. women. We analyzed population-based data from a 2013 study of U.S. women who were premenopausal, age 18–50, sexually active with a male partner in the last year and were not attempting pregnancy. Perceived discrimination was measured using the Everyday Discrimination Scale. Contraceptive method use was categorized into five method categories: permanent, highly effective reversible, moderately effective, barrier and no method. We analyzed relationships between perceived discrimination and contraceptive method use with several regression models, controlling for covariates. Among 539 women in our analytic sample, those with high perceived discrimination had lower incomes, less educational attainment and were less likely to be insured. Perceived discrimination was associated with a reduced odds of using any contraceptive method (aOR 0.43, CI 0.21–0.87, p < .001). Contraceptive method users with high perceived discrimination had an increased odds of using highly effective reversible methods versus moderately effective methods (aOR 5.28, CI 1.63–17.07 p = < .001). Women who perceived discrimination were at risk for contraceptive nonuse; however, among contraceptive users, perceived discrimination was associated with the use of more effective reversible methods.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; contraception; cours; discipline; discriminations; intersectionnalité; inégalités; justice reproductive; médecine; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; santé; sciences; sex2283; sexisme; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexual citizenship through resistance: a movement that centers disabled women’s voices - MacKeigan, Tanya (Disability & Society, 2021)
This research examines the discourses that shape disabled women’s sexual subjectivity. I wanted to see how disabled women’s understanding of themselves as sexual is socially influenced. I held a focus group and individually interviewed five self-identified physically disabled women about their sexual lives. They shared detailed stories of personal experiences and societal influences. The main social influences that were present in the women’s stories were ableism, sexism, and resistance; the focus of this article is resistance. Resistance discourses challenge mainstream notions of disability and sexuality and combat the oppression that ableism and sexism can create. It is important work to highlight these resistance narratives; they are often overlooked in society. Diverse social understandings of disability and sexuality are needed, and it is important that they come from disabled people. This research seeks to make space for disabled perspectives in the interest of sexual inclusivity and sexual citizenship for disabled women.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; EDI; accessibilité; amériques; approches et analyses; canada; capacitisme; care; colombie-britannique; corps; cours; discipline; droit des personnes en situation de handicap; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex1911; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Féminismes et pop culture - Padjemi, Jennifer (Éditions Stock, 2021)
"Dans un essai passionné et engagé, Jennifer Padjemi explore l'alliance, pour le meilleur et pour le pire, des féminismes et de la pop culture. A partir des mouvements féministes modernes, elle décortique le rapport que nous entretenons avec les objets culturels les plus populaires. En utilisant la pop culture comme un miroir de notre société mondialisée, l'auteure interroge les liens d'interdépendance entre consommation de masse et idéologie progressiste, et jette un regard joyeux et lucide sur nos divertissements, sans concession au patriarcat."–Quatrième de couverture.
Section: 283 pages ; 18 cm.
Keywords: afro-féminisme; approches et analyses; care; communication; corps; cours; discipline; féminisme afropéen; féminisme pop; féminismes noirs; intersectionnalité; journalisme; premier cycle; sex2283; sexualité; thématiques; écriture des femmes*; études culturelles

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap